Functional polystability of some nonautonomous quasilinear differential systems - Vitrychenko, I. E. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
For quasilinear differential systems with a boundary matrix of coefficients of the system of the first approximation, we obtain sufficient conditions of functional polystability, which generalizes the notion of exponential polystability.